2013
DOI: 10.1111/bju.12367
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen doubling time as a progression criterion in an active surveillance programme for patients with localized prostate cancer

Abstract: The uncertainty of calculated PSAdt during AS leads to a significant risk of patients being misclassified in terms of risk of progression, which limits the use of PSAdt in the management of patients on AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…These findings underline the relevance of a second opinion histopathological evaluation or discussion in uro‐pathological conferences in borderline cases. Still, compared with the considerable uncertainty and variation in the estimation of PSA doubling time , our present results indicate that the definition of ‘progression’, when based on the histopathological evaluation, is more reliable than when based on PSA kinetics alone. Gleason score reclassification between diagnostic and re‐biopsies may represent an actual disease progression with deteriorated prognosis and a subsequent survival benefit from curative treatment.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These findings underline the relevance of a second opinion histopathological evaluation or discussion in uro‐pathological conferences in borderline cases. Still, compared with the considerable uncertainty and variation in the estimation of PSA doubling time , our present results indicate that the definition of ‘progression’, when based on the histopathological evaluation, is more reliable than when based on PSA kinetics alone. Gleason score reclassification between diagnostic and re‐biopsies may represent an actual disease progression with deteriorated prognosis and a subsequent survival benefit from curative treatment.…”
Section: Discussionmentioning
confidence: 58%
“…Dynamic parameters including PSA kinetics, histopathological findings on re‐biopsies, and clinical tumour category (cT) are used to monitor selected patients with prostate cancer managed by active surveillance (AS) . However, recent reports have indicated that PSA kinetics are unreliable as progression criteria owing to the low specificity and wide CIs of the estimates .…”
Section: Introductionmentioning
confidence: 99%
“…Results from the existing active surveillance protocols also report similar proportions of patients who had a higher Gleason score or larger tumor burden at the time of the first repeated biopsy after diagnosis . Importantly, of the components typically included in active surveillance, findings at repeat biopsy may be the strongest indicator of adverse findings at radical prostatectomy …”
Section: Active Surveillance: Expectant Management With Curative Intentmentioning
confidence: 80%
“…PSA velocity can correlate with upgrading on prostatic re-biopsies and prostatectomy but the correlation with PSA doubling time is poor. [24][25][26][27][28] Active surveillance patients had 3-4 monthly PSA checks in our study. Similar to previous studies, PSA velocity has been used as a trigger, intentionally or unintentionally, for template biopsies in our study as the median PSA for initial transrectal ultrasound guided prostatic biopsies is 6.1 ng/ml and template biopsies is 6.7 ng/ml.…”
Section: Discussionmentioning
confidence: 99%